Augmented reality as an interactive multimedia in developing student's visual intelligence on molecular geometry material - Sari, Lily Widya; Dwiningsih, Kusumawati (Universitas Islam Negeri Raden Intan Lampung, 2025)
Being abstract and diverse, molecular shape material necessitates two or three-dimensional visualization media. This research seeks to develop interactive AR learning multimedia to enhance molecular geometry comprehension and students' visual intelligence. This study focuses on the development phase by employing the 4D Research and Development model, encompassing defining, designing, developing, and disseminating. Instruments include pre-tests, post-tests, student questionnaires, and validation sheets. Validation yields content and construct validity scores of 3 and 4, indicating valid or very valid criteria. Practicality exceeds 90%, deemed very practical. Effectiveness testing reveals that over 80% of students who achieved n-gain scores above 0.3 were classified as medium to high. These findings establish AR-based learning media as feasible for grasping molecular geometry and fostering visual intelligence. The implications of this research highlight AR's capacity to reinforce conceptual understanding and stimulate visual intelligence. Therefore, strategically optimizing technology-driven learning media like AR is crucial to align with the evolving digital landscape in education.